Pengaruh Integrated Marketing Communication pada Keputusan Pembelian Konsumen Toko Lautan Pasifik - Putri, Nova Kirana; Haryono, Cosmas Gatot (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2025)
The main challenge faced by labor-intensive industrial businesses such as the furniture industry in the digital era and tight industrial competition is how to attract consumer attention and interest effectively. Many business actors are not yet able to convey marketing messages optimally through appropriate communication channels, resulting in low purchasing decisions. This research aims to determine how much influence the Integrated Marketing Communication (IMC) strategy has on consumer purchasing decisions at the Lautan Pasifik Furniture Store. The approach used in this research is an explanatory quantitative approach, with a sample size of 100 respondents who are consumers of Mebel Lautan Pasifik. Data were collected through distributing questionnaires, then analyzed using simple linear regression analysis techniques. The results of the research show that there is a significant influence between Integrated Marketing Communication and consumer purchasing decisions. This research shows that the more effective the marketing communication strategy implemented, the higher the likelihood of consumers making a decision to purchase furniture products. This research also strengthens the application of the Stimulus-Organism-Response Theory, where communication strategies can shape consumer perceptions and attitudes in influencing interest in carrying out buying and selling which then encourages purchasing decisions. The practical implication of this research is the need for furniture business actors to manage marketing communications in an integrated manner to increase competitiveness and customer loyalty in a competitive market.